Akomodasi Komunikasi dalam Interaksi Antarbudaya antara Warga Asli Dusun Kiuteta dengan Warga Timor Leste di Desa Noelbaki - Windy Jullyan Funay; Blajan Konradus; Ferly Tanggu Hana (Jurnal Communio : Jurnal Jurusan Ilmu Komunikasi, 2019)
The purpose of this research is to find out the accommodation in convergence, divergence and excessive accommodation in intercultural interactions that occur between the original residents of Kiuteta hamlet and new residents of Kiuteta hamlet and new residents of Timor Leste in the village of Noelbaki, Kupang. The theory used in this study is the theory of communication accommodation. This research is a type of qualitative research. Data collection techniques used are interviews, observation, and documentation. Informants in this study amounted to 11 people, namely : (1) five new residents of Timor Leste, (2) five residents of the Kiuteta Hamlet, (3) Noelbaki Village leader. The results of this study indicate that in conversation people have three choices namely convergence, divergence, and excessive accommodation. Intercultural interaction of communication accommodation of convergence between indigenous residents of the Kiuteta Hamlet and new residents of Timor Leste, namely mutual respect when speaking and adjusting language where new residents of Timor Leste must adjust, understand the language use of the native inhabitants of the Kiuteta Hamlet. Convergence choices occur in some new residents of Timor Leste who still maintain a culture (dialect) to highlight differences. An act of excessive accommodation at an interaction where new residents of Timor Leste are considered as rude citizens. Suggestions for achieving common goals in diversity the adaptation process should continue to be carried out by local residents and new residents of Timor Leste in Kiuteta hamlet.